Sociocultural animation and professional formation in tourism: reflexions about touristic animation - Lacerda, Leonardo Lincoln Leite de (2009)
The present text brings some key points that are characteristics of the current discussions on Sociocultural Animation. It also approaches aspects referring to the field of tourism and it has the pretension of contributing to the reflections on it and simultaneously bringing new elements to observe the tourist experience. The importance of these ideas lies on the need of broadening the debates on Sociocultural Animation and on the possibility of showing the Tourist Animation as a relevant construct to reflections/ intervention. A bibliographical research centered on Sociocultural Animation and Tourism was used as means to this end. At the end, we hope that the proposal of establishing a narrower relation between the two animations does not stimulate the fragmentation of Sociocultural. On the contrary, we hope it will stimulate other fields of knowledge to contribute to the configuration of Sociocultural Animation.